2020
DOI: 10.1007/s10096-020-03831-w
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial vaginosis-associated vaginal microbiota is an age-independent risk factor for Chlamydia trachomatis, Mycoplasma genitalium and Trichomonas vaginalis infections in low-risk women, St. Petersburg, Russia

Abstract: The large majority of studies investigating associations between bacterial vaginosis (BV) and sexually transmitted infections (STIs) have been conducted among predominantly young women with high risk for STIs. Since a risky sexual behavior is a significant risk factor for both STIs and BV, this creates a bias toward an increased association between BV and STIs. This study evaluated associations between BV-associated vaginal microbiota and STIs (Chlamydia trachomatis, Mycoplasma genitalium, Trichomonas vaginali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 44 publications
4
18
0
2
Order By: Relevance
“…In terms of the usefulness of the MinION™ sequencer in gynecological practice, it is interesting that we were able to show the detailed condition of vaginal dysbiosis in a short period of time, which was not noted by the Nugent score. It has been suggested that vaginal dysbiosis may have a connection with the incidence of sexually transmitted infections (Shipitsyna, et al, 2020) and genital viral infections (Borgogna, et al, 2020) (Hoang, et al, 2020) or cervical lesions (Dahoud, et al, 2019). It has also been shown that metagenomic analysis using NGS applications to assess vaginal microbiota can provide more accurate results than conventional methods such as the Nugent score, Amsel's criteria, and bacterial cultures (van den Munckhof, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the usefulness of the MinION™ sequencer in gynecological practice, it is interesting that we were able to show the detailed condition of vaginal dysbiosis in a short period of time, which was not noted by the Nugent score. It has been suggested that vaginal dysbiosis may have a connection with the incidence of sexually transmitted infections (Shipitsyna, et al, 2020) and genital viral infections (Borgogna, et al, 2020) (Hoang, et al, 2020) or cervical lesions (Dahoud, et al, 2019). It has also been shown that metagenomic analysis using NGS applications to assess vaginal microbiota can provide more accurate results than conventional methods such as the Nugent score, Amsel's criteria, and bacterial cultures (van den Munckhof, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the usefulness of the MinION™ sequencer in gynecological practice, it is interesting that we were able to show the detailed condition of vaginal dysbiosis in a short period of time, which was not noted by the Nugent score. It has been suggested that vaginal dysbiosis may have a connection with the incidence of sexually transmitted infections [22] and genital viral infections [23,24] or cervical lesions [25]. The full-length 16S rRNA analysis using MinION™ could be a promising option for bacterial identification in a reasonable time frame for diagnostic purposes.…”
Section: Discussionmentioning
confidence: 99%
“…BV is the most common vaginal microbial disorder of women of childbearing age, and can lead to adverse obstetrics and gynecological outcomes such as infertility, miscarriage, premature rupture of membranes, and premature delivery ( Workowski and Bolan, 2015 ; Baqui et al., 2019 ; Peebles et al., 2019 ). It also increases the risk of sexually transmitted infections ( Shipitsyna et al., 2020 ). BV is characterized by an increase in the diversity of vaginal microbiota, a decrease in Lactobacillus spp.…”
Section: Common Reproductive Tract Infectionsmentioning
confidence: 99%
“…However, L. iners produces less lactic acid, so the microbiota dominated by L. iners increases the risk of C. trachomatis infection ( Van Houdt et al., 2018 ). Similarly, BV also increases the risk of C. trachomatis infection due to a reduction in the lactate concentration ( Shipitsyna et al., 2020 ). Therefore, C. trachomatis infection is greatly affected by lactic acid in the reproductive tract microenvironment.…”
Section: Common Reproductive Tract Infectionsmentioning
confidence: 99%
“…Vaginal anaerobic dysbiosis, bacterial vaginosis (BV), affects women’s self-esteem and sex life [ 1 ] and is associated with poor reproductive and obstetric sequelae [ 2 , 3 , 4 ]. An indicator of BV is the presence of ‘clue cells,’ which are desquamated vaginal epithelial cells coated with a biofilm [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%